Forced punching molded product, polyarylene sulfide resin composition, and method for producing forced punching molded product
A PAS resin composition with a specific filler blend and TD/MD ratio addresses deformation issues in forced punching, improving dimensional accuracy and mechanical strength of PAS molded products.
Patent Information
- Application Number
- JP2024519360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-10-18
- Filing Date
- 2023-09-21
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-09-21
AI Technical Summary
Existing methods for suppressing deformation during forced punching of polyarylene sulfide (PAS) resin molded products are insufficient, leading to issues such as increased components and fragile joints in complex shapes.
A PAS resin composition is developed by blending PAS resin with a specific amount of powdery inorganic filler, maintaining a TD/MD ratio of tensile modulus at 0.7 to 1.0, to suppress deformation in cylindrical parts during forced punching.
The composition effectively reduces deformation and maintains dimensional accuracy in PAS molded products, enhancing their appearance and mechanical strength.
Smart Images

Figure 0007608682000009 
Figure 0007608682000010 
Figure 0007608682000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a force-punched molded article, a polyarylene sulfide resin composition, and a method for producing the force-punched molded article. [Background technology]
[0002] In recent years, engineering plastics that are excellent in productivity and moldability as well as high heat resistance have been developed, and because they are lightweight, they are widely used as alternative materials to metal materials in electrical and electronic equipment, automobiles, etc. In particular, polyarylene sulfide (hereinafter sometimes abbreviated as PAS) resins, such as polyphenylene sulfide (hereinafter sometimes abbreviated as PPS) resins, are widely used in fields such as automotive parts and electrical and electronic equipment because they have excellent heat resistance, mechanical strength, chemical resistance, moldability, and dimensional stability.
[0003] PAS resin is often used as a material for parts with complex shapes. When a part with a complex shape is constructed by combining multiple parts, issues arise such as an increase in the number of parts, an increase in the number of manufacturing processes, and an increase in weak joints, so it is preferable to mold it as a single piece. When performing one-piece molding, for example, for piping parts with a bulge at the tip, force-pull molding may be performed. In force-pull molding, the mold is pulled out in the axial direction over the bulge of the molded product, so the bulge of the molded product needs to deform inward moderately (ideally elastically deform).
[0004] In relation to the above, a resin composition for force-punched molded products has been proposed that prevents deformation from remaining in molded products obtained by force-punching by specifying the flexural modulus of the resin composition (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 045032 Summary of the Invention [Problem to be solved by the invention]
[0006] However, these methods do not sufficiently suppress deformation during forced punching of resin molded products, and further improvements are required.
[0007] Therefore, the problem that the present invention aims to solve is to provide a PAS molded product in which deformation of the cylindrical portion after force-punching is suppressed, a PAS resin composition capable of providing such a molded product, and a method for producing the same. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above-mentioned problems, the inventors discovered that by combining a specific amount of filler with PAS resin, deformation of the cylindrical portion of a PAS resin molded product after force-punch molding can be suppressed, and thus completed the present invention.
[0009] That is, the forced punching molded product according to one embodiment of the present disclosure is A forced punch molded product having a cylindrical portion formed from a PAS resin composition obtained by blending a PAS resin (A) and an inorganic filler (B), The cylindrical portion has an undercut-shaped bulge that protrudes radially outward at a tip portion thereof, the inner surface of the cylindrical portion has a step in the outer diameter direction at the tip portion, and the inner diameter of the cylindrical portion excluding the step has a gradient such that the inner diameter of the cylindrical portion increases toward the tip portion, and the inorganic filler (B) contains a powdery inorganic filler (B1), the powdery inorganic filler (B1) is 15 to 180 parts by volume relative to 100 parts by volume of the PAS resin (A); It is characterized in that the TD / MD ratio of the tensile modulus at 150°C is 0.7 to 1.0.
[0010] The PAS resin composition according to one embodiment of the present disclosure comprises: A PAS resin composition for punch molding comprising a PAS resin (A) and an inorganic filler (B), The inorganic filler (B) contains a powdery inorganic filler (B1), the powdery inorganic filler (B1) is 15 to 180 parts by volume relative to 100 parts by volume of the PAS resin (A); It is characterized in that the TD / MD ratio of the tensile modulus at 150°C is 0.7 to 1.0.
[0011] A method for producing a PAS resin composition according to one embodiment of the present disclosure includes: A method for producing a PAS resin composition for force-punching, comprising a step of blending a PAS resin (A) and an inorganic filler (B) and melt-kneading the mixture at a temperature range equal to or higher than the melting point of the PAS resin (A), The inorganic filler (B) contains a powdery inorganic filler (B1), The composition is characterized in that the powdery inorganic filler (B1) is contained in an amount of 15 to 180 parts by volume relative to 100 parts by volume of the PAS resin (A).
[0012] In a method for producing a force-punched molded product according to an embodiment of the present disclosure, the force-punched molded product is produced by melt molding.
[0013] The present disclosure relates to a method for using the above-described force-pulling molded product as a piping member that comes into contact with a liquid or the like. Effect of the Invention
[0014] According to the present disclosure, it is possible to provide a PAS force-punch molded product in which deformation of the cylindrical portion after force-punch molding is suppressed, a PAS resin composition capable of providing such a molded product, and a method for producing the same. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a perspective view of a main part of a force-punched molded product according to one embodiment of the present disclosure, and is a schematic diagram of the force-punched molded product used in the examples. [Diagram 2]FIG. 2 is a cross-sectional view of a main part of the forced punching molded product of FIG. [Diagram 3] FIG. 3 is a diagram for explaining the forced punching of the forced punching molded product of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] <Forced punching molded products> Hereinafter, a force-punched molded product 1 according to an embodiment of the present disclosure will be described with reference to the drawings. In the drawings used in the following description, the shapes and dimensional relationships of the elements shown may differ from the shapes and dimensional relationships of the actual force-punched molded product 1.
[0017] FIG. 1 is a perspective view of the main part of a force-pulled molded product 1 according to this embodiment. In this embodiment, the main part of the force-pulled molded product 1 includes a cylindrical part 10 having a bulging part 11. FIG. 2 is a cross-sectional view of the force-pulled molded product 1 taken along line AA in FIG. 1. The force-pulled molded product 1 is formed by injection molding a PAS resin composition and forcing it out at the time of demolding. FIG. 3 is a diagram for explaining the force-pulling of the force-pulled molded product 1 in FIG. 1. Here, the force-pulling is a molding method in which a mold 30 overcomes the bulging part 11 of the molded product and is pulled out in the axial direction. The PAS resin composition is a composition obtained by blending a PAS resin and a fibrous filler. The PAS resin composition will be described in detail later.
[0018] In this embodiment, the cylindrical portion 10 of the force-punched molded product 1 has an undercut-shaped bulge 11 that protrudes in the outer diameter direction in a certain range (tip portion 16) in the axial direction from the tip 15. Here, the cylindrical portion 10 has a cylindrical shape with two circular bottom surfaces centered on the axis CA, and both of the two bottom surfaces are open. In other words, the cylindrical portion 10 has a hollow pipe shape with the tip 15 and the end 17 being open. The outer diameter direction is a direction perpendicular to the axial direction, which is a direction along the axis CA, and is a direction from the axis CA toward the side surface.
[0019] As shown in Fig. 1, the end 17 of the cylindrical portion 10 may be connected to another portion of the force-punched product 1. That is, the end 17 of the cylindrical portion 10 is located at a position farthest in the axial direction from the tip 15 such that the cross section has a circular shape centered on the axis CA. Here, the shape of the cylindrical portion 10 is symmetrical about the axis CA. For example, the two cross sections of the cylindrical portion 10 shown in Fig. 2 are vertically symmetrical about the axis CA.
[0020] 2, the outer surface 21 of the cylindrical portion 10 extends in the axial direction from the end 17 toward the tip 15 until it reaches the tip portion 16. Then, at the tip portion 16, the outer surface 21 is connected to a bulging portion 11 whose apex 12 protrudes most in the outer radial direction.
[0021] The inner surface 22 of the cylindrical portion 10 has a step 13 in the outer diameter direction at the tip portion 16. The inner surface 22 of the cylindrical portion 10 has a gradient such that the inner diameter of the cylindrical portion 10 increases from the end 17 toward the tip portion 16 except for the step 13. In this embodiment, the gradient is constant. The step 13 is connected to the inner surface 22 of the cylindrical portion 10 except for the step 13 at a connecting portion 14. Here, the inclined portion 18 shown in FIG. 2 is a portion having a constant gradient from the end 17 toward the tip portion 16, that is, the inner surface 22 of the cylindrical portion 10 except for the step 13. The connecting portion 14 is located at the end of the inclined portion 18 on the tip 15 side.
[0022] As shown in Fig. 3, the cylindrical portion 10 having the bulge 11 is formed by force removal. When releasing from the mold, the die 30 is pulled out in the axial direction from the end 17 toward the tip portion 16. At this time, a force from the die 30 is applied to the bulge 11, and the tip portion 16 is bent toward the axis CA with the corner 14a at the step 13 as a fulcrum.
[0023] In this embodiment, the value of the undercut rate is not limited. However, from the viewpoint of preventing molding defects such as breakage due to elastic deformation of the bulging portion 11 during forced demolding, the undercut rate is preferably 20% or less, more preferably 14% or less. Further, from the viewpoint of preventing detachment when the bulging portion 11 is inserted into a flexible tube, pipe, or the like, the undercut rate is preferably 5% or more, more preferably 3.5% or more.
[0024] Here, the undercut rate is determined by the following formula (c).
[0025]
Equation
[0026] As shown in FIG. 2, the outer diameter C in formula (c) is the outer diameter of the cylindrical portion 10 at the top 12 of the bulging portion 11.
[0027] As shown in FIG. 2, the outer diameter B in formula (c) is the outer diameter of the cylindrical portion 10 excluding the bulging portion 11.
[0028] The forced demolding molded product 1 according to this embodiment preferably has a roundness retention rate of 90% or more, more preferably 95% or more, for the cylindrical portion 10. Thereby, a molded product with excellent appearance can be obtained. The roundness retention rate is a value calculated from the values measured by a dimensional measuring machine by the method described in the examples.
[0029] The forced demolding molded product 1 according to this embodiment preferably has an arithmetic mean height Sa of the inner wall surface of the bulging portion 11 of 60 [μm] or less, more preferably 50 [μm] or less. Further, the maximum height Sz of the inner wall surface of the bulging portion 11 is preferably 350 [μm] or less, more preferably 300 [μm] or less. The arithmetic mean height Sa and the maximum height Sz are values measured by the method described in the examples in accordance with ISO 25178.
[0030] <PAS resin composition> The above-mentioned punched molded product 1 is formed from a PAS resin composition obtained by blending a PAS resin (A) and an inorganic filler (B). The PAS resin composition described below (the PAS resin composition of the present disclosure) may be used exclusively for the punched molded product 1.
[0031] The PAS resin composition of the present disclosure contains a PAS resin (A) as an essential component. The PAS resin (A) has a resin structure having a repeating unit in which an aromatic ring and a sulfur atom are bonded, and specifically, the PAS resin (A) is represented by the following general formula (1):
[0032] [ka] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group.
[0033] [ka] The trifunctional structural moiety represented by formula (2) is preferably present in an amount of 0.001 to 3 mol %, particularly preferably 0.01 to 1 mol %, based on the total number of moles of the trifunctional structural moiety and other structural moieties.
[0034] Here, the structural portion represented by the general formula (1) is particularly R 1 and R 2 is preferably a hydrogen atom from the viewpoint of the mechanical strength of the PAS resin, and in that case, examples include those bonded at the para position represented by the following formula (3) and those bonded at the meta position represented by the following formula (4).
[0035] [ka] Among these, a structure in which the bond between the sulfur atom and the aromatic ring in the repeating unit is at the para position represented by the general formula (3) is particularly preferred in terms of the heat resistance and crystallinity of the PAS resin.
[0036] The PAS resin may include not only the structural moieties represented by the general formula (1) or (2) but also the structural moieties represented by the following structural formulae (5) to (8):
[0037] [ka] The structural moieties represented by the general formulae (1) and (2) may account for 30 mol % or less of the total of the structural moieties represented by the general formulae (1) and (2). In particular, in the present disclosure, it is preferable that the structural moieties represented by the general formulae (5) to (8) account for 10 mol % or less in terms of the heat resistance and mechanical strength of the PAS resin. When the PAS resin contains the structural moieties represented by the general formulae (5) to (8), the bonding mode thereof may be either a random copolymer or a block copolymer.
[0038] The PAS resin may have naphthyl sulfide bonds or the like in its molecular structure, but the amount of such bonds is preferably 3 mol % or less, and particularly preferably 1 mol % or less, based on the total molar amount including other structural portions.
[0039] As a method for crosslinking a PAS resin, a method can be used in which a low molecular weight linear polymer obtained by condensation polymerization of a monomer mainly composed of a bifunctional halogenated aromatic compound represented by the above general formula (1) is heated at a high temperature in the presence of oxygen or an oxidizing agent to increase the melt viscosity by crosslinking or thermal crosslinking, or a method can be used in which a small amount of a monomer such as a polyhalo aromatic compound having three or more halogen functional groups represented by the above general formula (2) is used during condensation polymerization to form a partially branched structure or crosslinked structure.
[0040] The physical properties of the PAS resin (A) are not particularly limited as long as they do not impair the effects of the present invention, and are as follows.
[0041] (Melt Viscosity) The melt viscosity of the PAS resin (A) is not particularly limited, but in order to obtain a good balance between fluidity and mechanical strength, the melt viscosity (V6) measured at 300°C is preferably in the range of 2 Pa·s or more, and preferably in the range of 1000 Pa·s or less, more preferably in the range of 500 Pa·s or less, and further preferably in the range of 200 Pa·s or less. The melt viscosity (V6) is measured using a Shimadzu flow tester, CFT-500D, at 300°C, load: 1.96×10 6 The melt viscosity is measured after holding the sample for 6 minutes at a pressure of 1 Pa and L / D = 10 (mm) / 1 (mm).
[0042] (Non-Newtonian Exponents) The non-Newtonian index of the PAS resin (A) is not particularly limited, but is preferably in the range of 0.90 or more to 2.00 or less. When a linear type PAS resin is used, the non-Newtonian index is preferably in the range of 0.90 or more, more preferably 0.95 or more to preferably 1.50 or less, more preferably 1.20 or less. Such a PAS resin is excellent in mechanical properties, fluidity, and abrasion resistance. However, the non-Newtonian index (N value) is a value calculated using the following formula by measuring the shear rate (SR) and shear stress (SS) using a capillary rheometer under the conditions of melting point +20°C and the ratio of the orifice length (L) to the orifice diameter (D) L / D=40. The closer the non-Newtonian index (N value) is to 1, the closer the structure is to a linear structure, and the higher the non-Newtonian index (N value), the more branched the structure is.
[0043]
number
[0044] (Manufacturing method of PAS resin) The method for producing the PAS resin (A) is not particularly limited, but examples thereof include (production method 1) a method in which a dihalogeno aromatic compound is polymerized in the presence of sulfur and sodium carbonate, and if necessary, a polyhalogeno aromatic compound or other copolymerization component is added, (production method 2) a method in which a dihalogeno aromatic compound is polymerized in a polar solvent in the presence of a sulfidizing agent or the like, and if necessary, a polyhalogeno aromatic compound or other copolymerization component is added, (production method 3) a method in which p-chlorothiophenol is added, and if necessary, other copolymerization components are added, and self-condensation is performed, and (production method 4) a method in which a diiodo aromatic compound and elemental sulfur are melt-polymerized under reduced pressure in the presence of a polymerization inhibitor that may have a functional group such as a carboxy group or an amino group. Among these methods, (production method 2) is preferred because it is versatile. During the reaction, an alkali metal salt of a carboxylic acid or sulfonic acid or an alkali hydroxide may be added to adjust the degree of polymerization. Among the above-mentioned (Production Method 2) methods, there is a method for producing a PAS resin by introducing a water-containing sulfidizing agent into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and then reacting the dihalogeno aromatic compound and the sulfidizing agent in the organic polar solvent, and optionally adding a polyhalogeno aromatic compound, and controlling the amount of water in the reaction system to within a range of 0.02 to 0.5 mol per mol of the organic polar solvent (see JP-A-07-228699). Particularly preferred is a method in which a dihalogeno-aromatic compound and, if necessary, a polyhalogeno-aromatic compound or other copolymerization component are added in the presence of potassium metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted while controlling the organic acid alkali metal salt in the range of 0.01 to 0.9 mol per mol of the sulfur source and the amount of water in the reaction system to 0.02 mol or less per mol of the aprotic polar organic solvent (see WO2010 / 058713 pamphlet).Specific examples of the dihalogenoaromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-di Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, 1,4,6-trihalonaphthalene, etc. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.
[0045] The method for post-treating the reaction mixture containing the PAS resin obtained by the polymerization step is not particularly limited, and examples thereof include (post-treating 1) a method in which, after the completion of the polymerization reaction, the reaction mixture is first distilled off under reduced pressure or normal pressure, either as is or after the addition of an acid or base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having a similar solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried; or (post-treating 2) a method in which, after the completion of the polymerization reaction, the reaction mixture is dissolved in a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (a solvent that is soluble in the polymerization solvent used and is a poor solvent for at least PAS). or (post-treatment 3) after the polymerization reaction is completed, the reaction mixture is added with a reaction solvent (or an organic solvent having a solubility equivalent to that of the low molecular weight polymer) and stirred, and then the mixture is filtered to remove the low molecular weight polymer, and then the mixture is washed once or twice or more times with a solvent such as water, acetone, methyl ethyl ketone, or an alcohol, and then neutralized, washed with water, filtered, and dried; (post-treatment 4) after the polymerization reaction is completed, the reaction mixture is added with water, washed with water, filtered, and if necessary, an acid or base is added during the water washing, and then the mixture is dried; or (post-treatment 5) after the polymerization reaction is completed, the reaction mixture is filtered, and if necessary, the mixture is washed once or twice or more times with the reaction solvent, and then washed with water, filtered, and dried. In any of the post-treatment methods, the reactivity, crystallization rate, sodium content, etc. of the PAS resin can be controlled by adjusting the pH by adding an acid or base during the water-washing step, and the pH after the hot water-washing step can be controlled to be in the range of 6.5 to 11.5, more preferably in the range of 6.5 to 8.5.
[0046] In the post-treatment methods exemplified above in (Post-treatment 1) to (Post-treatment 5), the PAS resin may be dried in a vacuum, or in air or in an inert gas atmosphere such as nitrogen.
[0047] The PAS resin (A) used in this embodiment may be a PAS resin newly polymerized by the above method, or a recycled PAS resin. For example, a PAS resin recovered from a PAS resin composition or a PAS resin molded product may be used. Specifically, a PAS resin obtained by heating a PAS resin composition or a PAS resin molded product in an organic polar solvent to dissolve the PAS contained therein and performing the above-mentioned post-treatment on the solution may be used. In addition, a PAS resin composition or a PAS resin molded product mechanically crushed may be used as the PAS resin. Specifically, a sprue or runner generated during the manufacture of a molded product, a product recovered as a non-standard molded product, or a molded product once used as a product may be crushed. In this case, a crushed product of a PAS resin composition or a PAS resin molded product containing a component other than the PAS resin may be used.
[0048] <Inorganic filler (B)> The PAS resin composition of the present disclosure is prepared by blending an inorganic filler (B). The inorganic filler (B) uses a powdered inorganic filler (B1) as an essential component. In addition, a plate-like inorganic filler (B2) and a fibrous inorganic filler (B3) can be used as optional components.
[0049] As the raw material for the inorganic filler (B) applicable to the present disclosure, those known to those skilled in the art can be used, and the fiber diameter, fiber length, aspect ratio, and the like can be appropriately adjusted depending on the application of the molded article.
[0050] The inorganic filler (B) applicable to the present disclosure may be one that has been treated with a surface treatment agent or a sizing agent. This is preferable because it can improve the adhesive strength with the PAS resin (A). Examples of the surface treatment agent or sizing agent include at least one polymer selected from the group consisting of silane compounds having functional groups such as amino groups, epoxy groups, isocyanate groups, and vinyl groups, titanate compounds, acrylic resins, urethane resins, polyether resins, and epoxy resins, and in particular, those containing urethane resins are preferable from the viewpoint of suppressing excessive defibration during processing. When the surface treatment agent or sizing agent contains urethane resin, its content is not particularly limited, but from the viewpoint of fuel swelling resistance, it is preferably in the range of 35 mass% or less, and more preferably in the range of 20 mass% or less.
[0051] The amount of the inorganic filler (B) is preferably 40 parts by volume or more, more preferably 50 parts by volume or more, and even more preferably 60 parts by volume or more, relative to 100 parts by volume of the PAS resin (A) from the viewpoint of obtaining better mechanical strength, while the amount is preferably 180 parts by volume or less, more preferably 140 parts by volume or less, and even more preferably 90 parts by volume or less, from the viewpoint of the flowability and processability of the resin composition.
[0052] The powdered inorganic filler (B1) applicable to the present disclosure can be a known and commonly used material, and can be, for example, a filler of various shapes such as a plate-like or powdered one.Specific examples include graphite, silica, quartz powder, glass beads, silicates such as calcium silicate, aluminum silicate, and diatomaceous earth, metal oxides such as iron oxide, titanium oxide, zinc oxide, and alumina, metal carbonates such as calcium carbonate and magnesium carbonate, metal sulfates such as calcium sulfate and barium sulfate, silicon carbide, silicon nitride, boron nitride, and various metal powders, and one or more of them can be appropriately selected according to the required performance.Among them, calcium carbonate and glass beads can be preferably used.
[0053] The average particle diameter (D 50The range of the average particle diameter (D) is not particularly limited, but from the viewpoint of excellent mechanical strength and flowability, it is preferably in the range of 100 μm or less, more preferably in the range of 50 μm or less, even more preferably in the range of 20 μm or less, and particularly preferably in the range of 2 μm or less. The average particle diameter is the average particle diameter (D) calculated based on the particle size distribution measured in a conventional manner using a laser diffraction scattering type particle size distribution measuring device (Microtrac MT3300EXII). 50 ).
[0054] The amount of powdery inorganic filler (B1) in the PAS resin composition of the present disclosure is not particularly limited as long as it does not impair the effects of the present invention, but is preferably in the range of 15 parts by volume or more, more preferably 30 parts by volume or more, and even more preferably 40 parts by volume or more, relative to 100 parts by volume of PAS resin (A), and is preferably 180 parts by volume or less, more preferably 140 parts by volume or less, and even more preferably 90 parts by volume or less. Within such a range, the resin composition has good fuel swelling resistance and moldability, especially releasability, and the molded product exhibits high dimensional accuracy, which is preferable.
[0055] The plate-like inorganic filler (B2) applicable to the present disclosure can be any known and commonly used material, such as glass flake, talc, mica, kaolin, clay, alumina, various metal foils, etc., and one or more of them can be appropriately selected according to the required performance. Among these, it is preferable to use glass flake from the viewpoint of mechanical strength and ease of handling.
[0056] The amount of the plate-like inorganic filler (B2) in the PAS resin composition of the present disclosure is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 80 parts by volume or less, more preferably 50 parts by volume or less, and even more preferably 10 parts by volume or less, relative to 100 parts by volume of the powdery inorganic filler (B1). In such a range, the resin composition has good fuel swelling resistance and moldability, especially releasability, and the molded product exhibits high dimensional accuracy, which is preferable.
[0057] The fibrous inorganic filler (B3) applicable to the present disclosure may be any known or commonly used material, such as glass fiber, carbon fiber, silica fiber, silica-alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate fiber, wollastonite, and metal fibrous materials such as stainless steel, aluminum, titanium, copper, and brass, and one or more of these may be appropriately selected according to the required performance. Among these, glass fiber is preferably used from the viewpoint of mechanical strength and ease of handling.
[0058] The amount of the fibrous inorganic filler (B3) in the PAS resin composition of the present disclosure is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 230 parts by volume or less, more preferably 130 parts by volume or less, still more preferably 100 parts by volume or less, and particularly preferably 20 parts by volume or less, relative to 100 parts by volume of the powdery inorganic filler (B1). In such a range, the resin composition has good fuel swelling resistance and moldability, especially releasability, and the molded product exhibits high dimensional accuracy, which is preferable.
[0059] The PAS resin composition of the present disclosure may contain a silane coupling agent as an optional component, if necessary. The silane coupling agent is not particularly limited as long as it does not impair the effects of the present invention, but a silane coupling agent having a functional group that reacts with a carboxy group, such as an epoxy group, an isocyanato group, an amino group, or a hydroxyl group, is preferably used. Examples of such silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane. In the present disclosure, the silane coupling agent is not an essential component, but when it is added, the amount of the silane coupling agent is not particularly limited as long as it does not impair the effects of the present invention, and is preferably in the range of 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, to preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the PAS resin (A). In such a range, the resin composition has good moldability, especially releasability, and the mechanical strength of the molded product is improved, which is preferable.
[0060] The PAS resin composition of the present disclosure may contain a thermoplastic elastomer as an optional component, if necessary. Examples of the thermoplastic elastomer include polyolefin-based elastomers, fluorine-based elastomers, and silicone-based elastomers, among which polyolefin-based elastomers are preferred. When these elastomers are added, the amount of the elastomers is not particularly limited as long as it does not impair the effects of the present invention, but is preferably in the range of 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, to preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the PAS resin (A). In this range, the impact resistance of the resulting PAS resin composition is improved, which is preferable.
[0061] For example, the polyolefin-based elastomer may be a homopolymer of an α-olefin, a copolymer of two or more α-olefins, or a copolymer of one or more α-olefins and a vinyl polymerizable compound having a functional group. In this case, the α-olefin may be an α-olefin having 2 or more to 8 or less carbon atoms, such as ethylene, propylene, or 1-butene. In addition, the functional group may be a carboxy group, an acid anhydride group (-C(=O)OC(=O)-), an epoxy group, an amino group, a hydroxyl group, a mercapto group, an isocyanate group, or an oxazoline group. Examples of the vinyl polymerizable compound having the functional group include one or more of vinyl acetate, α,β-unsaturated carboxylic acids such as (meth)acrylic acid, alkyl esters of α,β-unsaturated carboxylic acids such as methyl acrylate, ethyl acrylate, and butyl acrylate, metal salts of α,β-unsaturated carboxylic acids such as ionomers (metals include alkali metals such as sodium, alkaline earth metals such as calcium, and zinc), glycidyl esters of α,β-unsaturated carboxylic acids such as glycidyl methacrylate, and the like, α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid, and derivatives of the α,β-unsaturated dicarboxylic acids (monoesters, diesters, and acid anhydrides). The above-mentioned thermoplastic elastomers may be used alone or in combination of two or more.
[0062] Furthermore, in addition to the above components, the PAS resin composition of the present disclosure may further contain synthetic resins such as polyester resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene ether resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylate resin, polyethylene resin, polypropylene resin, polyethylenetetrafluoroethylene resin, polyethylenedifluoroethylene resin, polystyrene resin, ABS resin, phenol resin, urethane resin, and liquid crystal polymer as optional components depending on the application. Although the synthetic resin is not an essential component in the present disclosure, when it is added, the ratio of the synthetic resin to be added is not particularly limited as long as it does not impair the effects of the present invention, and it differs depending on each purpose and cannot be generally defined, but the ratio of the synthetic resin to be added in the resin composition of the present disclosure is, for example, in the range of 5 parts by mass or more and 15 parts by mass or less per 100 parts by mass of PAS resin (A). In other words, the ratio of the PAS resin to the total of the PAS resin (A) and the synthetic resin is preferably in the range of (100 / 115) or more, and more preferably in the range of (100 / 105) or more, on a mass basis.
[0063] In addition, the PAS resin composition of the present disclosure may contain other known and commonly used additives as optional components, such as colorants, antistatic agents, antioxidants, heat stabilizers, UV stabilizers, UV absorbers, foaming agents, flame retardants, flame retardant assistants, rust inhibitors, and release agents (metal salts or esters of fatty acids having 18 to 30 carbon atoms, including stearic acid or montanic acid, polyolefin waxes such as polyethylene, etc.). These additives are not essential components, and may be used in an amount of, for example, preferably 0.01 parts by mass or more, and preferably 1000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the PAS resin (A), as appropriate for the purpose or use so as not to impair the effects of the present invention.
[0064] The PAS resin composition of the present disclosure has a small anisotropy of the tensile modulus at 150°C. Specifically, the TD / MD ratio is in the range of 0.7 to 1.0. In this range, deformation of the molded product before and after the force-pulling process in the molding process can be suppressed, and the dimensional accuracy is excellent. In order for the PAS resin composition to have the above properties, it is effective to adjust the blending amount of the inorganic filler (B), and this can be achieved, for example, by adjusting the amount of the powdery inorganic filler (B1), which is an essential component, and the plate-like inorganic filler (B2) and fibrous inorganic filler (B3), which are optional components. The TD / MD ratio of the tensile modulus at 150°C in the present disclosure is a value measured in accordance with the method of the examples. In the present disclosure, MD refers to the flow direction of the resin in molding, and refers to a direction with a fiber orientation parameter of 0.9 or more. On the other hand, TD refers to a direction perpendicular to the flow direction of the resin in molding, and refers to a direction with a fiber orientation parameter of 0.1 or less. The closer the TD / MD ratio is to 1, the smaller the anisotropy of the elastic modulus is.
[0065] The tensile modulus of the PAS resin composition of the present disclosure at room temperature (23°C) is not particularly limited, but is preferably 15 [GPa] or less, more preferably 8 [GPa] or less. In this range, deformation of the molded product before and after the forcible removal process in the molding process can be suppressed, and dimensional accuracy is excellent, which is preferable. The tensile modulus in the present disclosure is a value measured by a method conforming to ISO 527-1 and 2 using an ISO Type-A dumbbell piece obtained by injection molding the PAS resin composition.
[0066] The method for producing a PAS resin composition disclosed herein is a method for producing a PAS resin composition for force-punching, comprising a step of blending a PAS resin (A) and an inorganic filler (B) as essential components, and melt-kneading them at a temperature range equal to or higher than the melting point of the PAS resin (A), characterized in that the inorganic filler (B) contains a powdery inorganic filler (B1), and the powdery inorganic filler (B1) is present in an amount of 15 to 180 parts by volume per 100 parts by volume of the PAS resin (A). The method is described in detail below.
[0067] The method for producing a PAS resin composition of the present disclosure includes a step of blending the above essential components and melt-kneading them at a temperature range equal to or higher than the melting point of the PAS resin (A). More specifically, the PAS resin composition of the present disclosure is composed of each essential component and, if necessary, other optional components. Methods for producing a resin composition applicable to the present disclosure are not particularly limited, but include a method of blending the essential components and, if necessary, optional components, and melt-kneading them, and more specifically, a method of uniformly dry-mixing them, if necessary, in a tumbler or Henschel mixer, and then feeding them into a twin-screw extruder and melt-kneading them.
[0068] The melt kneading can be carried out by heating the resin to a temperature range in which the resin temperature is equal to or higher than the melting point of the PAS resin (A), preferably equal to or higher than the melting point + 10°C, more preferably equal to or higher than the melting point + 10°C, even more preferably equal to or higher than the melting point + 20°C, preferably equal to or lower than the melting point + 100°C, more preferably equal to or lower than the melting point + 50°C.
[0069] The melt kneader is preferably a twin-screw kneading extruder from the viewpoint of dispersibility and productivity. For example, it is preferable to melt knead while appropriately adjusting the resin component discharge amount in the range of 5 to 500 (kg / hr) and the screw rotation speed in the range of 50 to 500 (rpm), and it is more preferable to melt knead under the condition that the ratio (discharge amount / screw rotation speed) is in the range of 0.02 to 5 (kg / hr / rpm). In addition, each component may be added and mixed to the melt kneader simultaneously or in portions. For example, when adding the inorganic filler (B), which is an essential component among the components, it can be fed into the extruder from a side feeder of the twin-screw kneading extruder. The position of the side feeder is preferably such that the ratio of the distance from the extruder resin input part (top feeder) to the side feeder to the total screw length of the twin-screw kneading extruder is 0.1 or more, more preferably 0.3 or more. In addition, such a ratio is preferably 0.9 or less, more preferably 0.7 or less.
[0070] The PAS resin composition of the present disclosure obtained by melt kneading in this manner is a molten mixture containing the essential components, optional components added as necessary, and components derived therefrom. Therefore, the PAS resin composition of the present disclosure has a morphology in which the PAS resin (A) forms a continuous phase and other essential components and optional components are dispersed. After the melt kneading, the PAS resin composition of the present disclosure is preferably pre-dried at a temperature range of 100 to 150°C by a known method, for example, by extruding the molten resin composition into a strand shape, and then processing it into a form such as pellets, chips, granules, or powder.
[0071] The molded article of the present disclosure is obtained by melt molding a PAS resin composition. The manufacturing method of the molded article of the present disclosure includes a step of melt molding the PAS resin composition. Therefore, the molded article of the present disclosure has a morphology in which the PAS resin (A) forms a continuous phase and other essential components and optional components are dispersed. When the PAS resin composition has such a morphology, a molded article having excellent fuel swelling resistance and mechanical strength can be obtained.
[0072] The PAS resin composition of the present disclosure can be subjected to various molding processes such as injection molding, compression molding, extrusion molding of composites, sheets, pipes, etc., pultrusion molding, blow molding, and transfer molding, but is particularly suitable for injection molding applications because it has excellent releasability. When molding by injection molding, various molding conditions are not particularly limited, and molding can be performed by a normal general method. For example, in an injection molding machine, the PAS resin composition is melted at a resin temperature in a temperature range of the melting point of the PAS resin (A) or higher, preferably in a temperature range of the melting point +10°C or higher, more preferably in a temperature range of the melting point +10°C to the melting point +100°C, and even more preferably in a temperature range of the melting point +20 to the melting point +50°C, and then the resin is injected into a mold from a resin outlet and molded. At that time, the mold temperature may also be set to a known temperature range, for example, room temperature (23°C) to 300°C, preferably 130 to 190°C.
[0073] The method for producing a PAS resin molded article of the present disclosure includes a step of annealing the molded article. The optimum conditions for the annealing treatment are selected depending on the application or shape of the molded article, and the annealing temperature is preferably in the range of 100°C or more, and more preferably in the range of 120°C or more. On the other hand, it is preferably in the range of 260°C or less, and more preferably in the range of 240°C or less. The annealing time is not particularly limited, but is preferably in the range of 0.5 hours or more, and more preferably in the range of 1 hour or more. On the other hand, it is preferably in the range of 10 hours or less, and more preferably in the range of 8 hours or less. In such a range, the distortion of the obtained molded article is reduced and the crystallinity of the resin is improved, which is preferable. The annealing treatment may be performed in air, but is preferably performed in an inert gas such as nitrogen gas.
[0074] The molded article according to the present embodiment includes a remolded article obtained by reusing a molded article obtained by melt-molding the PAS resin composition. Specifically, for example, the molded article includes a sprue or runner generated during the manufacture of a molded article, a molded article recovered as a non-standard molded article, or a molded article once used as a product, which is washed as necessary, crushed, and melt-molded again at a temperature equal to or higher than the melting point of the PAS resin. When reusing, it is preferable from the viewpoint of mechanical properties to mix the crushed molded article with the PAS resin composition. The size of the molded article when crushed is not particularly limited, but it is preferable that the size is about the same as that of the PAS resin composition to be mixed from the viewpoint of mixability and processability. In addition, the mixing ratio is preferably 50 parts by mass or less of the crushed molded article relative to 100 parts by mass of the PAS resin composition, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less. In such a range, the recyclability can be improved without impairing the effect of the PAS resin composition of the present disclosure.
[0075] The PAS resin molded product of the present disclosure is characterized by excellent force-pullout moldability, and is therefore particularly suitable for parts made using a force-pullout mold die. Examples include piping, containers, joints, valve bodies, etc., and more specifically, it can be suitably used for various parts that come into contact with liquid or steam, such as pipes, lining pipes, cap nuts, pipe joints (elbows, headers, tees, reducers, joints, couplers, etc.), various valves, flow meters, gaskets (seals, packings, etc.). In addition, the molded product of the present disclosure can also be made into the following ordinary resin molded products. For example, protective and supporting materials for box-shaped electric and electronic component integrated modules, multiple individual semiconductors or modules, sensors, LED lamps, connectors, sockets, resistors, relay cases, switches, coil bobbins, capacitors, variable capacitor cases, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, terminal blocks, semiconductors, liquid crystal displays, FDD carriages, FDD chassis, motor brush holders, parabolic antennas, computer-related parts, and other representative electric and electronic parts; VTR parts, television parts, irons, headsets, etc. Home and office electrical appliance parts such as air dryers, rice cooker parts, microwave oven parts, audio parts, audio / visual equipment parts such as audio / laser discs, compact discs, DVD discs, and Blu-ray discs, lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, and water-related equipment parts such as water heaters, bath water volume and temperature sensors; office computer related parts, telephone related parts, facsimile related parts, copier related parts, cleaning jigs, motor parts, lighters, typewriters, and other machine related parts; optical equipment and precision machinery related parts such as microscopes, binoculars, cameras, and watches;Alternator terminals, alternator connectors, brush holders, slip rings, IC regulators, potentiometer bases for light dimmers, relay blocks, inhibitor switches, various valves such as exhaust gas valves, various pipes for fuel, exhaust and intake systems, air intake nozzle snorkels, intake manifolds, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors, brake pad wear sensors, throttle position sensors, crankshaft position sensors, temperature sensors, air flow meters, brake pad wear sensors, thermostat bases for air conditioners, heating hot air flow control valves, radiators Examples of automotive and vehicle related parts include brush holders for motors, water pump impellers, turbine vanes, wiper motor related parts, distributors, starter switches, ignition coils and bobbins, motor insulators, motor rotors, motor cores, starter relays, transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, coils for fuel-related electromagnetic valves, fuse connectors, horn terminals, electrical component insulating plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, and other various applications. EXAMPLES
[0076] The present invention will be described below using examples and comparative examples, but is not limited to these examples. In the following, unless otherwise specified, "%" and "parts" are based on volume.
[0077] <Examples 1 to 7 and Comparative Examples 1 to 4> Each material was mixed according to the composition and mixing amounts shown in Tables 1 and 2. The mixed materials were then fed into a vented twin-screw extruder "TEX-30α (product name)" manufactured by Japan Steel Works, Ltd., and melt-kneaded at a resin component discharge rate of 30 kg / hr, a screw rotation speed of 200 rpm, and a set resin temperature of 320°C to obtain pellets of the resin composition. The glass fiber was fed from the side feeder (S / T ratio 0.5), and the other materials were mixed uniformly in a tumbler beforehand and fed from the top feeder. The pellets of the resin composition obtained were dried in a gear oven at 140°C for 2 hours, and then injection molded to produce various test pieces, and the following tests were performed.
[0078] <Evaluation>
[0079] (1) Evaluation of tensile properties The obtained pellets were fed into a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set at 310°C, and injection molding was performed using an ISO Type-A dumbbell specimen molding die with a mold temperature controlled at 140°C to obtain ISO Type-A dumbbell specimens. The resin was injected from a single gate to produce test specimens that did not include welds. The tensile modulus and tensile elongation at break of the obtained dumbbell specimens at room temperature were measured using the measurement methods in accordance with ISO 527-1 and 2. The results are shown in Tables 1 and 2.
[0080] (2) Measurement of TD / MD ratio of tensile modulus at 150℃ Injection molding was performed using a 100 x 100 x 2 mmt mold under the same conditions as in (1) to obtain a sheet-shaped molded product. The obtained molded product was used to cut dumbbells (ISO Type 1BA) for tensile tests in the resin flow direction (MD) and in the direction perpendicular to the MD direction (TD). The tensile modulus of the obtained dumbbell pieces at 150°C was measured using a measurement method based on ISO 527-1 and 2, and the TD / MD ratio was calculated. The results are shown in Tables 1 and 2.
[0081] (3) Measurement of surface roughness (Sa and Sz) of punched products The obtained pellets were fed to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set at 310°C, and injection molded using a mold with a forced extraction structure with a mold temperature controlled at 140°C to obtain a molded product in a pipe shape (inner diameter φ11.5, undercut ratio 15). The presence or absence of cracks on the inner diameter side surface of the pipe tip was visually confirmed, and if there were cracks, the surface roughness (arithmetic mean height Sa and maximum height Sz) of the cracked area was measured in accordance with ISO 25178 using a 3D dimension measuring machine (Keyence Corporation "VR-5200"). If large and deep cracks occurred, Sa and Sz showed larger values. The results are shown in Tables 1 and 2.
[0082] (4) Evaluation of circularity retention rate of forced punch molded products An evaluation was performed using a molded product of the same pipe shape as in (3). The outer diameter direction dimension from the tip of the cylindrical part to the top of the bulge at the point (a) where the inner diameter side tilt of the pipe tip is the largest and the point (b) where it is the smallest (the dimension from the tip 15 of the cylindrical part 10 to the top 12 of the bulge 11 in Fig. 2) was measured using a 3D dimension measuring machine (Keyence Corporation "VR-5200"). From the measured values, the roundness was calculated using the following formula. The closer the roundness is to 100%, the more deformation is suppressed. The results are shown in Tables 1 and 2. Roundness retention rate [%] = (b) dimension [mm] / (a) dimension [mm] x 100
[0083] [Table 1]
[0084] [Table 2]
[0085] ·PAS resin (A) PPS resin A-1: Linear type, melt viscosity (V6) 40 Pa·s, non-Newtonian index 1.16
[0086] ·Inorganic filler (B) B-1: Powdered inorganic filler, glass beads, Union Co., Ltd. UB-02EG, particle size (D 50 ) 19.5μm B-2: Powdered inorganic filler, calcium carbonate, Sankyo Seifon Co., Ltd. calcium carbonate Class 1, particle size (D 50 ) 1.7μm B-3: Plate-shaped inorganic filler, glass flake, Nippon Sheet Glass REFG-301, base flake average particle size 160 μm, thickness 5 μm B-4: Fibrous inorganic filler, glass fiber, Nippon Electric Glass Co., Ltd. ECS03T-725H, fiber diameter: 10 μm, fiber length: chopped strand of 3 mm
[0087] Other Ingredients C-1: Elastomer, Bondfast 7L, manufactured by Sumitomo Chemical Co., Ltd.
[0088] From Tables 1 and 2, it is clear that the molded products of the Examples have smaller surface roughness and a higher circularity retention rate than the molded products of the Comparative Examples, and therefore deformation during force-punching is suppressed. [Explanation of symbols]
[0089] 1. Forced punching molded products 10 Cylindrical part 11 Bulge 12 Top 13 Steps 14 Connection part 14a corner 15 Tip 16 Tip part 17 Terminal 18 Slope 21 Exterior 22 Inner Surface 30 Mold
Claims
1. A forced punch molded product having a cylindrical portion formed from a polyarylene sulfide resin composition obtained by blending a polyarylene sulfide resin (A) and an inorganic filler (B), The cylindrical portion has an undercut-shaped bulge that protrudes in an outer diameter direction at a tip portion, the inner surface of the cylindrical portion has a step in the outer diameter direction at the tip portion, and the inner diameter of the cylindrical portion excluding the step has a gradient such that the inner diameter of the cylindrical portion increases toward the tip portion; the inorganic filler (B) includes a powdery inorganic filler (B1) and a fibrous inorganic filler (B3); the powdery inorganic filler (B1) is 15 to 180 parts by volume per 100 parts by volume of the polyarylene sulfide resin (A), and the fibrous inorganic filler (B3) is 130 parts by volume or less per 100 parts by volume of the powdery inorganic filler (B1); A punched product having a TD / MD ratio of tensile modulus at 150°C of 0.7 to 1.
0.
2. Furthermore, the inorganic filler (B) contains at least a plate-like inorganic filler (B2), 2. The force-punched molded product according to claim 1, wherein the plate-like inorganic filler (B2) is in a range of 60 parts by volume or less per 100 parts by volume of the powdery inorganic filler (B1).
3. A forced punch molded product as described in claim 1 or 2, characterized in that the tensile modulus at 23°C is 15 GPa or less.
4. The force-punched molded product according to claim 1 or 2, wherein the circularity retention rate of the cylindrical portion is 90% or more. (The circularity retention rate is a value calculated by measuring the outer diameter direction dimensions from the tip of the cylindrical portion to the top of the bulge at the point (a) where the inner diameter side inclination of the cylindrical portion is the largest and the point (b) where the inner diameter side inclination is the smallest, using a dimension measuring machine, and calculating the circularity retention rate from the following formula.) Roundness retention rate [%] = (b) dimension [mm] / (a) dimension [mm] x 100
5. 3. The punched product according to claim 1, wherein the arithmetic mean height Sa of the inner wall of the bulge, as measured by a size measuring machine, is 60 [μm] or less, and the maximum height Sz is 350 [μm] or less.
6. A polyarylene sulfide resin composition for force-punching, comprising a polyarylene sulfide resin (A) and an inorganic filler (B), The inorganic filler (B) contains a powdery inorganic filler (B1) and a fibrous inorganic filler (B3), the powdery inorganic filler (B1) is 15 to 180 parts by volume per 100 parts by volume of the polyarylene sulfide resin (A), and the fibrous inorganic filler (B3) is 130 parts by volume or less per 100 parts by volume of the powdery inorganic filler (B1); A polyarylene sulfide resin composition for force-punching, characterized in that the TD / MD ratio of the tensile modulus at 150°C is 0.7 to 1.
0.
7. Furthermore, the inorganic filler (B) contains a plate-like inorganic filler (B2), 7. The polyarylene sulfide resin composition for force-punching according to claim 6, wherein the amount of the plate-like inorganic filler (B2) is in the range of 60 parts by volume or less per 100 parts by volume of the powdery or granular inorganic filler (B1).
8. A polyarylene sulfide resin composition for force-punching according to claim 6 or 7, characterized in that the tensile modulus at 23°C is 15 GPa or less.
9. The polyarylene sulfide resin composition for force-punching according to claim 6 or 7, which is a melt-kneaded product.
10. A method for producing a polyarylene sulfide resin composition for force-punching, comprising a step of blending a polyarylene sulfide resin (A) and an inorganic filler (B) and melt-kneading the mixture at a temperature range equal to or higher than the melting point of the polyarylene sulfide resin (A), The inorganic filler (B) contains a powdery inorganic filler (B1) and a fibrous inorganic filler (B3), the powdery inorganic filler (B1) is 15 to 180 parts by volume per 100 parts by volume of the polyarylene sulfide resin (A); the fibrous inorganic filler (B3) is 130 parts by volume or less per 100 parts by volume of the powdery inorganic filler (B1); A method for producing a polyarylene sulfide resin composition for force-punching, comprising the steps of:
11. Furthermore, the inorganic filler (B) contains a plate-like inorganic filler (B2), 11. The method for producing a polyarylene sulfide resin composition for force-punching according to claim 10, characterized in that the amount of the plate-like inorganic filler (B2) is in the range of 60 parts by volume or less per 100 parts by volume of the powdery inorganic filler (B1).
12. A method for producing a polyarylene sulfide resin composition for force-punching according to claim 10 or 11, characterized in that the tensile modulus at 23°C is 15 GPa or less.
13. 12. A method for producing a force-pull molded product, comprising: a step of producing a polyarylene sulfide resin composition by the method according to claim 10 or 11; and a step of injection molding using a mold having a force-pull structure.
14. A method for using the forced punching molded product according to claim 1 or 2 as a member that comes into contact with liquid or steam.
Citation Information
Patent Citations
Rolling bearing retainer
JP2002021854A
Polyarylene sulfide resin composition
JP2003128915A
Polyamide resin composition and molded body
JP2015013984A
Polyphenylene sulfide resin composition for forcibly pulling injection molding
JP2018141083A
Resin composition, molded article, and method for producing same
WO2019045032A1